Chronic gastrointestinal inflammation in a dog mimicking human russell body gastroduodenitis - Cervone, Mario; Duboy, Julie; Laprie, Caroline; Abadie, Jérôme (Brazilian Journal of Veterinary Pathology, 2017)
Herein we describe an unusual benign chronic gastroduodenal inflammation associated with protein losing enteropathy in a dog. A 10-year-old Golden Retriever dog was presented for chronic weight loss associated with pica, ptyalism, vomiting and diarrhea. Blood chemistry showed hypoproteinaemia and hypoalbuminaemia. Gastric and duodenal full-thickness biopsies were collected and histopathological examination revealed severe mucosal infiltration with Mott cells, consistent with Russell body gastroduodenitis in humans. Warthin-starry stain showed no Helicobacter spp. proliferation in gastric biopsies. After treatment including anti-acid, antibiotics and corticosteroids, no recurrence of gastrointestinal signs was reported and improvement in clinical and biological condition was observed.